ANALISIS DAMPAK PERNIKAHAN DINI TERHADAP CERAI GUGAT DI DESA BETET KECAMATAN KEPOHBARU, BOJONEGORO - Sakinah; Rohmawati, Nanda; Ramadan, Mohammad Naufal (Universitas Islam Negeri Alauddin Makassar, 2024)
The research aims to explain the impact of early marriage on divorce in Betet Village, Kepohbaru District, Bojonegoro. Early marriage in this study is a marriage that occours at the age of less than 19 years. The theory used in this research is the theory of social action from Max Weber (1864-1920) which is a theory that emerged because each person’s assumptions are different according to what they feel and according to what is needed for the good of themselves and others. The approach used in this research is qualitative with a descriptive design. This research aims to provide a careful description of certain individuals or groups regarding the conditions and symptoms that occur. The results of the research show views on early marriage, including several social action concepts originating from the views of teenagers, parents, elders and other communities regarding early marriages carried out in Betet Village. The reason is, because of arranged marriages, coercion, and the lack of economic factors In the family, and view the previous people in Betet Village, were eligible for early marriage because the were arranged in an arragend marriage in 2001 without any mutual liking, but as time goes by, feelings will definitely arise like. With social action weber emphasizes responding to a social problem rationally according to circumstances or needs.